Guest

(x – 2) + (x – 3) + (x – 9) = 0 (x – 2) + (x – 3) + (x – 9) = 0 (x – 2) + (x – 3) + (x – 9) = 0 (x – 2) + (x – 3) + (x – 9) = 0

(x – 2) + (x – 3) + (x – 9) = 0
(x – 2) + (x – 3) + (x – 9) = 0
(x – 2) + (x – 3) + (x – 9) = 0
(x – 2) + (x – 3) + (x – 9) = 0
 

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5963 Points
2 years ago
Dear Student

(x – 2) + (x – 3) + (x – 9) = 0

x – 2 + x – 3 + x – 9 = 0

3x – 2 – 3 – 9 = 0

3x – 14 = 0

x = 14/3

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free